Wakaf Digital di Kalangan Generasi Z Ditinjau dari Perspektif Etika Ekonomi Islam - Rini Hayati Lubis; Nurul Izzah (Journal of Islamic Social Finance Management, 2026)
This study aims to analyze the practice of digital waqf among Generation Z from the perspective of Islamic economic ethics. Generation Z is a group that has a high level of digital literacy and is very close to the use of technology, so it has great potential in the development of digital-based Islamic philanthropy. This research uses a qualitative method with a library research approach through the analysis of various literature related to digital waqf, characteristics of Generation Z, and the principles of Islamic economic ethics. The results of the study show that digital waqf is in line with the ethical values of Islamic economics if it is managed based on the principles of justice ('adl), trust, transparency, social responsibility, and benefits (maslahah). Ease of access, flexibility of transactions, and the use of technology are factors that encourage Generation Z's interest in participating in digital waqf. However, there are still several challenges, such as low waqf literacy, the level of trust in management institutions, and understanding of the sharia-compliant digital waqf mechanism. Therefore, it is necessary to strengthen accountable digital governance, improve waqf education, and optimize the use of digital media to increase Generation Z's participation in digital waqf. This research contributes to the development of the study of Islamic philanthropy by highlighting the relationship between technological innovation, the participation of the younger generation, and the implementation of Islamic economic ethics in the digital era.